Individualizing busulfan dose in specific populations and evaluating the risk of pharmacokinetic drug-drug interactions. (1st February 2023) - Combarel, David; Tran, Julie; Delahousse, Julia; Vassal, Gilles; Paci, Angelo
ABSTRACT: Introduction: Busulfan is an alkylating agent widely used in the conditioning of hematopoietic stem cell transplantation possessing a complex metabolism and a large interindividual and intra-individual variability, especially in children. Combined with the strong rationale of busulfan PK/PD relationships, factors altering its clearance (e.g. weight, age, and GST-A genetic polymorphism mainly) can also affect clinical outcomes. Areas covered: This review aims to provide an overview of the current knowledge on busulfan pharmacokinetics, its pharmacokinetics variabilities in pediatric populations, drug-drug interactions (DDI), and their consequences regarding dose individualization. This review was based on medical literature up until October 2021. Expert opinion: To ensure effective busulfan exposure in pediatrics, different weight-based nomograms have been established to determine busulfan dosage and provided improved results (65–80% of patients correctly exposed). In addition to nomograms, therapeutic drug monitoring (TDM) of busulfan measuring plasmatic concentrations to estimate busulfan pharmacokinetic parameters can be used. TDM is now widely carried out in routine practices and aims to ensure the targeting of the reported therapeutic windows by individualizing busulfan dosing based on the clearance estimations from a previous dose.